Identification for Development : Cote d’Ivoire - Atick, Joseph J (World Bank, Washington, DC, 2016)
The report is organized into the following sections: section two presents the approach and methodology of the evaluation used. It gives an overview of the Identification Systems Analysis (ISA). Section three gives a detailed description of the Identity ecosystem in Cote d’Ivoire. It examines all the identification schemes that were considered of primary importance by the Mission and that were part of the interviews conducted. Where enough data was collected, the ISA analysis is performed and the color coded score is presented. Section four presents a series of recommendations to address the identification needs of the WB Project but also for improving the identification practices in the country in general. Those recommendations are based on the extensive experience that the World Bank ISA team has had in the course of applying the tool in similar environments. In addition to these primary sections, the report contains four appendices: appendix one presents the scoring methodology of ISA. Appendix two provides a brief history of identification regulations in Côte d’Ivoire. It is meant to give some legal context to the identification schemes currently in place. Appendix three discusses how the foundation of current identity schemes (national identity card and the voter register) were dictated by the Peace Accord of Ouagadougou, and what role identity played in the conflict and the exit from that period. Appendix four is a detailed overview of the important law on privacy. The so called Law No. 2013-450 related to the protection of personally identifying information, which was adopted in 2013 and is currently being enforced systematically. This is the Côte d’Ivoire adaptation of the ECOWAS law on data protection and it represents a very significant body of codified legislation.